INSIDENSI SINDROM PASCA KOLESISTEKTOMI PADA PASIEN KOLELITIASIS - Ridhana, Achmad; Wibowo, Agung Ary; Yuliana, Ida; Rosida, Lena; Poerwosusanta, Hery (Universitas Lambung Mangkurat, 2024)
Abstract: Post-cholecystectomy syndrome can reduce the recovery of patients with cholelithiasis. This study aims to analyze the incidence of post-cholecystectomy syndrome in patients with cholelithiasis. This study was descriptive longitudinal co-hort prospective with follow up patients 2 and 7 days post cholecystectomy using guided interviews. The incidence of post-cholecystectomy syndrome based on clinical symptoms of 54 subjects 2 and 7 days postoperatively was 38.9% and 14.8%. Of the 54 subjects there were clinical symptoms of biliary colic pain 2 and 7 days after cholecystectomy, many felt moderate and mild pain, percentages of 50% and 88.9%. Fever 2 and 7 days after cholecystectomy many did not feel it percentage of 70.4% and 100%. Jaundice 2 and 7 days after cholecystectomy was mostly not felt by 90.7% and 98.1%. Jaundice 2 and 7 days after cholecystectomy was mostly not felt by 90.7% and 98.1%. Vomiting 2 and 7 days after cholecystectomy was not experienced by 74.1% and 88.9%, respectively. Dyspepsia 2 and 7 days after cholecystectomy was mostly not felt by 74.1% and 83.3%. Diarrhea 2 and 7 days after cholecystectomy was not experienced by 100% and 87%, respectively. Abdominal cramps 2 days after cholecystectomy were mostly felt by 87%, 7 days after cholecystectomy were mostly not felt by 92.6%. Most subjects 2 and 7 days post cholecystectomy did not experience post-cholecystectomy syndrome. Keywords: incidence, post cholecystectomy syndrome, cholelithiasis Abstrak: Sindrom pasca kolesistektomi dapat menurunkan kesembuhan pasien kolelitiasis. Penelitian bertujuan menganalisis insidensi sindrom pasca kolesistektomi pada pasien kolelitiasis. Penelitian ini deskriptif longitudinal co-hort prospektif dengan follow up pasien 2 dan 7 hari pasca kolesistektomi menggunakan wawancara terpimpin. Insidensi sindrom pasca kolesistektomi berdasarkan gejala klinis dari 54 subjek 2 dan 7 hari pasca operasi sebesar 38,9% dan 14,8%. Dari 54 subjek terdapat gejala klinis nyeri kolik bilier 2 dan 7 hari pasca kolesistektomi banyak merasakan nyeri sedang dan ringan persentase 50% dan 88,9%. Demam 2 dan 7 hari pasca kolesistektomi banyak tidak merasakannya persentase 70,4% dan 100%. Ikterus 2 dan 7 hari pasca kolesistektomi banyak tidak merasakannya persentase 90,7% dan 98,1%. Ikterus 2 dan 7 hari pasca kolesistektomi banyak tidak merasakannya persentase 90,7% dan 98,1%. Muntah 2 dan 7 hari pasca kolesistektomi banyak tidak merasakannya persentase 74,1% dan 88,9%. Dispepsia 2 dan 7 hari pasca kolesistektomi banyak tidak merasakannya persentase 74,1% dan 83,3%. Diare 2 dan 7 hari pasca kolesistektomi banyak tidak merasakannya persentase 100% dan 87%. Kram perut 2 hari pasca kolesistektomi banyak merasakannya persentase 87%, 7 hari pasca kolesistektomi banyak tidak merasakannya persentase 92,6%. Sebagian besar subjek 2 dan 7 hari pasca kolesistektomi tidak mengalami sindrom pasca kolesistektomi. Kata-kata kunci: insidensi, sindrom pasca kolesistetomi, kolelitiasis.